2002
DOI: 10.1046/j.1365-3180.2002.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of developmental stage and time of assessment on hot water weed control

Abstract: Summary The influence of plant developmental stage in hot water weed control was studied on the test weed Sinapis alba in field experiments. The dose was measured as thermal energy in the hot water (kJ m−2) and the response as reduction in plant weight. The energy dose for a 90% reduction in plant weight was 340 kJ m−2 at the two‐leaf stage, which is one‐third of the energy required for the same reduction at the six‐leaf stage. Treatment at an early stage saves energy, increases the driving speed and lowers th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 9 publications
(16 reference statements)
4
41
1
Order By: Relevance
“…In agreement with other studies (Hansson & Ascard, 2002;Kolberg & Wiles, 2002;Rifai eta/., 2002), this study demonstrated the importance of controlling weeds when they are in their early growth stage. For young weeds, the best treatment combinations were IR at 2.5 km h-1 for all species and OF at 1.5 km h-1 for all species except white mustard.…”
Section: Table4supporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with other studies (Hansson & Ascard, 2002;Kolberg & Wiles, 2002;Rifai eta/., 2002), this study demonstrated the importance of controlling weeds when they are in their early growth stage. For young weeds, the best treatment combinations were IR at 2.5 km h-1 for all species and OF at 1.5 km h-1 for all species except white mustard.…”
Section: Table4supporting
confidence: 93%
“…These percentages are all lower than those obtained with IR (all speeds) and OF (speeds of 1.5 and 2.5 km h-1 ). Compared with the results reported by Hansson & Ascard (2002), the HW unit performed poorly perhaps because the driving speeds were too fast for HW to be effective, and only one application was used.…”
Section: Table4mentioning
confidence: 61%
See 1 more Smart Citation
“…Among these tactics, the use of steaming promises to be useful because it efficiently transfers heat (Rask and Kristoffersen 2007) and reduces fire risk, especially in areas where dry plant residue is present (Hansson and Ascard 2002). However, there is limited information about the factors that determine the effectiveness of steaming as a POST weed control tactic.…”
mentioning
confidence: 99%
“…Pre-emergence thermal weeding using hot water (Kurfess and Kleisinger, 1999;Hansson and Ascard, 2002), steam (Kolberg and Wiles, 2002) or recycling hot air (Bertram, 1996) prevent fire hazards in dry residues but are relatively costly. Hot water applied to narrow strips (20% of the field area) with small weeds would require approximately 1.6 m 3 water ha À1 and 20 kg propane ha À1 (derived from Hansson and Ascard, 2002). Combining strip flaming and punch planting (Rasmussen, 2003) allows for crop establishment without soil disturbance, which reduces and delays weed germination.…”
Section: No-till Management Unitsmentioning
confidence: 99%